COVID-19 and food (in)security in Africa: Review of the emerging empirical evidence - Tabe-Ojong, Martin Paul Jr.; Nshakira-Rukundo, Emmanuel; Gebrekidan, Bisrat Haile (International Food Policy Research Institute, 2022)
COVID-19 risks rolling back many of the efforts and global successes recorded in reducing poverty and food insecurity. We undertake a systematic review of the growing microeconomic literature on the association between COVID-19 and food (in)security in Africa, discussing its implications for food policy and research. In doing so, we highlight some of the methodological weaknesses in answering policy-relevant questions on the causal link between COVID-19 and food insecurity. We also review the various coping strategies households are using to build resilience to COVID-19 and explore the role of social protection and other tools in mitigating some of the negative effects of COVID-19. This review provides evidence that COVID-19 is associated with food insecurity both ex-ante and ex-durante. There are many attempts to suggest this relationship may be causal with some robust methods in some contexts, but data limitations prevail which constrains causal learning. We also find evidence that income losses, loss of employment, and heightened food prices may be mediating the relationship between COVID-19 and food insecurity. Going further, we additionally review the mitigating role of social protection and remittances in reducing the negative effects of COVID-19 on food insecurity. Relatedly, we also show evidence that households are using various coping strategies such as food rationing and dietary change to cushion themselves against the COVID-19 shock but most of these measures remain adversely correlated with food insecurity. We end with a discussion on some potential interesting areas where future efforts can be geared to improve learning on the relationship between COVID-19, food insecurity, and building resilience to shocks.